Strategi Keamanan Siber Malaysia - Putri Bilqis Oktaviani; Anggraeni Silvia (Jurnal Kajian Ilmiah, 2021)
This research discusses the analysis of security strategy policies made by the Malaysian government in the protection and development of Malaysian cyberspace. This research will explain in detail the strategy of developing challenges as well as the aspects that support the Malaysian cyber space to be saved by the Malaysian cyber space. This research will further discuss the Malaysian security strategy through the official document of the Malaysian security strategy which will later be analyzed through the MAXQDA and GEPHI applications in order to classify the various categories that support it. This research will use the security concept published by Hao Yeli in Three - Perspective Theory of Cyber ​​Sovereignty to classify ideas and data. This research finds that the security of the Malaysian system needs to be developed from both capacity and capability so that the government needs to work together with various related parties Keywords: Cyber Security, Cybersecurity Challenges, Soveignty Abstrak Penelitian ini membahas tentang analisis kebijakan strategi keamanan siber yang dibuat oleh pemerintah Malaysia dalam perlindungan dan pengembangan keamanan ruang siber Malaysia. Penelitian ini akan menjelaskan secara details strategi, tantangan serta aspek – aspek yang mendukung pengembangan ruang siber Malaysia guna mengamankan ruang siber Malaysia. Penelitian ini akan membahas lebih jauh strategi keamanan Malaysia melalui dokumen resmi strategi keamanan siber Malaysia yang nantinya akan di bedah melalui aplikasi MAXQDA dan GEPHI guna mengklasifikasikan berbagai kategori yang mendukung. Penelitian ini akan menggunakan konsep keamanan yang dipublikasikan oleh Hao Yeli dalam A Three – Perspective Theory of Cyber Sovereignty guna mengkasifikasikan gagasan dan data dengan menggunakan metode penelitian kuantitatif. Penelitian ini menemukan bahwa keamanan siber Malaysia perlu dikembangkan baik dari kapasitas maupun kapabilitas sehingga pemerintah Malasyaia perlu bekerjasama dengan berbagai pihak yang terkait. Kata kunci: Cyber Security, Tantangan Keamanan Cyber, Kedaulatan